2018
DOI: 10.1108/reps-07-2018-003
|View full text |Cite
|
Sign up to set email alerts
|

The nexus between financial development and poverty reduction in Egypt

Abstract: Purpose-The purpose of this study is to empirically examine the impact of financial development on poverty reduction in Egypt. The paper also investigates whether financial development affects poverty via gross domestic product (GDP) growth. Design/methodology/approach-This study uses the autoregressive distributed lag approach to estimate two specifications. The first is dependent on poverty by the ratio domestic credit to the private sector (percentage of GDP) and the second is dependent on the poverty by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 60 publications
2
14
0
Order By: Relevance
“…Poverty is a concern of many governments in the world because it is closely related to economic growth. Many studies also confirm that poverty is an important factor in economic growth (Kheir, 2018;Sasmal & Sasmal, 2016;Sehrawat & Giri, 2016).…”
Section: Introduction 11 Backgroundmentioning
confidence: 92%
See 1 more Smart Citation
“…Poverty is a concern of many governments in the world because it is closely related to economic growth. Many studies also confirm that poverty is an important factor in economic growth (Kheir, 2018;Sasmal & Sasmal, 2016;Sehrawat & Giri, 2016).…”
Section: Introduction 11 Backgroundmentioning
confidence: 92%
“…The fulfillment of basic needs will bring good quality to human resources, to liberate people from poverty. Additionally, many studies confirm that poverty is an important factor in economic growth (Kheir, 2018;Sasmal & Sasmal, 2016;Sehrawat & Giri, 2016). Poverty is a situation where the annual income of individuals in an area cannot meet the minimum expenditure standards required by individuals to be able to live properly in the region.…”
Section: Economic Growthmentioning
confidence: 99%
“…Kheir [18] investigated the impact of Financial Market Development (FMD) on poverty in Egypt. The study considered the ARDL model for the sample period from 1980 to 2015 and found the significant role of FMD and money supply in reducing Egypt's poverty.…”
Section: The Impact Of Macroeconomic Factors On Povertymentioning
confidence: 99%
“…Odhiambo (2009) inspects the causality among financial development, poverty, and economic growth for the data of South Africa ranging the period 1960-2006 to find that both financial development and economic growth Granger-cause poverty reduction in the country. Kheir (2018), using the data covering the period 1980-2015, finds for another African nation, namely Egypt, that there exists bi-directional causality between financial development and poverty reduction both in the short-run and long run. The study uses the ratio of household final consumption expenditures to GDP as a proxy for poverty data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The present study aims at unearthing the effect of financial development on poverty reduction. We formulate the following model, in line with Beck et al (2007), Odhiambo (2009), and Kheir (2018) to assess the nature of the relationship.…”
Section: The Model and Datamentioning
confidence: 99%